A ferida aberta do empatronamento: colonialidade e resistência Ava guarani em Santa Cruz - Bolívia - ROSSEL, Graciela Violeta Majluf (2020)
The research proposes an analysis of the aspects of power coloniality exercised in the Ava guarani population of the municipality of Colpa Belgium, located one hour from the capital of the Santa Cruz de la Sierra Department. The unit of analysis is the impatronated population that works at Sugar Mill La Belgium, currently called Poplar Capital S / A. In this sense, this research proposes to analyze the working conditions in the sugar harvest since its arrival in the city until 2019. Therefore, we opted for the decolonial theory, to understand the objective and subjective process of coloniality and empatronation. of this population from the racial division of labor, concept provided by sociologist Anibal Quijano. In this sense, to understand the scope of coloniality, it is necessary to analyze the past events of the guarani population, so we are based on a historical perspective that details the historical events that led the Ava guarani to accept these working conditions. Once explained the process of migration we developed the subjective aspects of the colonization process of being from the analysis of Frantz Fanon, to study, later, the processes of resistance to the pain of the colonial wound, begging the art of arete guasu. Six months of data collection were performed using the qualitative method, ethnography, participant observation and semi-structured interviews. Historically, guarani Indians were persecuted to the point that they were given only two options: to serve or to die. Today in 2019, conditions of semi-slavery exist as the Ava guarani are seeking other forms of colonial resistance.